On the validity of the power gap law for rotational energy transfer in CO2-H2 collisions - Ibrahim Ali , Noorbatcha; N., Sathyamurthy (ELSEVIER Science B.V., 1981)
The validity of the power gap law for rotational energy transfer has been tested in the case of rigid-rotor CO2-H2 collisions The power law with a single parameter γ is shown to be adequate only for small amounts of energy transferred. For larger amounts, use of a different γ seems to be warranted suggesting a deficiency of the power law or operation of two mechanisms for rotational energy transfer.